Determinan Struktur Modal Pada Perusahaan Menufaktur Di Bursa Efek Indonesia - Yulianto, Agung (MEDIA EKONOMI & TEKNOLOGI INFORMASI, 2011)
Financing resource is very important to support firm activities. A number of theories have been proposed to explain the variation in debt ratios across firms. The theoris suggest that frims select capital structure depending on attributes that determine the various costs and benefits associated with debt and equite financing. Financial managers often think of the frim´s debt-equite decision as a trade-off between interesed tax shields and the cost of financial distress. This packing order theory of capital structure recoqniezes that target debt ratios may vary from firm to firm. Packing order theory states that frims prefer to finance new investement, first internally with retained earning, then with debt, and finally with an issue of new equity. Companies with safe, tangible assets and vollatility ought to have target ration. Unprofitable companies with risky, intangible assets ought to rely primarily on equity financing. This study aims to determine the factors that determine capital structure in coorperate policies in terms of variable tangibility, profitability, growth, volatility, cash holdings and firms size. Sample are all manufacturing companies listed in Indonesia Stock Excahange in the year 2005-2008. Sampling was done by purposive sampling method and obtained a simple of 532 frim years. The characteristics and properties af manufacturing companies serve as the research sample are manufacturing companies that reported financial statments in the rupiah currency periodically to Bapepam with the period of late December during the period 2005-2008. The analitical tool used is regrission analysis. Result of hypotesis testing indicate that tangibility significant positive influence to leverage therefore, collateral assets may increase the chace of loan companies. Prifitability is negatively related to leverage, this can happen because the study period there were 108 companies taht are experiencing a loss, but not significant, significant growth is negatively related with leverage, this means that companies tend to choose to fund companies using internal capital compared with do debt. Volatility is positively related to significant, as can be seen in changes in operating profit during the study peroid. Cash holdings significantly negatively assosiated with levarange, tend to use internal funding that comes from holding cash that trying debt. Firm size is positively assosiated with leverage, but not significant, explained that large compainies will have grater leverage to expand its business.Keyword: tangibility, profitability, growth, volatility, cash holdin, firm size and leverage.